A change of IL-2 and IL-4 production in patients with Helicobactor pylori infection. Issue 4 (1995) - Fan Fan, X. G. X. G.; Yakoob Yakoob, J. J.; Fan Fan, X. J. X. J.; Keeling Keeling, P. W. N. P. W. N.
Abstract : Hellcobacter pylori is the most common cause of gastroduodenal inflammation. However, the exact immune pathogenesis is not fully understood. To look for evidence of the immunological mechanism in H. pylori associated disease, we measured cytokine interleukin-2 (IL-2) and IL-4 levels produced by peripheral blood lymphocytes (PBL) and gastric biopsies in 20 subjects with or without H. pylori infection. H. pylori can stimulate IL-2 and IL-4 production from PBL in H. pylori negative as well as H. pylori positive individuals. The spontaneous IL-2 production by PBL and gastric biopsies was greater (p < 0.0025, <0.001)in H. pylori negative individuals than that in H. pylori infected patients. Increased IL-4 levels from PBL in H. pylori infected patients were found in the presence of H. pylori (p < 0.0025). An increased spontaneous production of IL-4 from gastric biopsies was also observed in H. pylori infected patients (p < 0.025). In conclusion, an enhanced type 2 cytokine production was observed in H. pylori infected patients, which may be responsible for H. pylori chronic infection.